Response surface methodology optimization for enhancing the analytical performance of a hanging mercury drop electrode for imidacloprid - Jessica Moreno Betancourth; Valeria Pfaffen (Results in Chemistry, 2024)
We introduce an innovative approach to enhance the quantification of the pesticide imidacloprid (IMD) using square wave voltammetry (SWV) with a mercury drop electrode (HMDE). Through systematic factorial designs, we meticulously adjusted both the chemical and instrumental parameters of SWV, with a particular focus on optimizing the peak reduction current. Using response surface methodology (RSM) provided comprehensive insights into the system behavior. The optimal conditions were found at a pH of IMD solution of 7.45, Accumulation Potential (Eacc) of −0.70 V, Accumulation Time (tacc) of 46.45 s, Frequency (F) of 200 Hz, Amplitude (Esw) of 0.090 V, and Step (dE) of 0.0080 V. With these optimized parameters, we constructed a calibration curve spanning a concentration range from 0.5 to 5.0 × 10-7 mol/L. The method exhibited a remarkably low limit of detection (LOD) at 3.65 × 10-8 mol/L and a limit of quantification (LOQ) of 5.01 × 10-8 mol/L. Subsequently, we rigorously assessed the methodology's effectiveness by quantifying IMD in various water samples from the Córdoba area, achieving consistently near 100 % recovery values.